Synthesis, X-ray diffraction analysis, quantum chemical studies and α-amylase inhibition of probenecid derived S-alkylphthalimide-oxadiazole-benzenesulfonamide hybrids - Bilal Ahmad Khan; Syeda Shamila Hamdani; Muhammad Naeem Ahmed; Shahid Hameed; Muhammad Ashfaq; Ahmed M. Shawky; Mahmoud A. A. Ibrahim; Peter A. Sidhom (Journal of Enzyme Inhibition and Medicinal Chemistry)
Sulphonamide and 1,3,4-oxadiazole moieties are present as integral structural parts of many drugs and pharmaceuticals. Taking into account the significance of these moieties, we herein present the synthesis, single-crystal X-ray analysis, DFT studies, and α-amylase inhibition of probenecid derived two S-alkylphthalimide-oxadiazole-benzenesulfonamide hybrids. The synthesis has been accomplished in high yields. The final structures of both hybrids have been established completely with the help of different spectro-analytical techniques, including NMR, FTIR, HR-MS, and single-crystal X-ray diffraction analyses. In an effort to confirm the experimental findings, versatile quantum mechanical calculations and Hirshfeld Surface analysis have been performed. α-Amylase inhibition assay has been executed to investigate the enzyme inhibitory potential of both hybrids. The low IC50 value (76.92 ± 0.19 μg/mL) of hybrid 2 shows the good α-amylase inhibition potential of the respective compound. Ultimately, the binding affinities and features of the two hybrids are elucidated utilising a molecular docking technique against the α-amylase enzyme.